UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI LISTRIK DINAMIS MELALUI METODE EKSPERIMEN - Sondang, Frederika (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This study aims to describe the implementation of experimental methods to improve science learning outcomes on electricity. This research is class action research (PTK). Each cycle consists of three stages of activities, namely planning, implementation of action and observation, and reflection. The subjects of this study were students of class 9C SMP Negeri 1 Tempuran Magelang Regency with a total of 32 students. Data collection in this study used teacher and student activity observation sheets and written tests. Data analysis techniques used were descriptive qualitative and descriptive quantitative with percentages. The results showed an increase in science learning outcomes of Dynamic Electricity material in class 9C SMP Negeri 1 Tempuran students after the implementation of learning with experimental methods in cycle I on average was 77.1875 after cycle II on average was 83.125. Behavioral changes that occur in class 9C students of SMP Negeri 1 Tempuran in the implementation of learning with experimental methods to improve science learning outcomes in Dynamic Electricity material include the following (a) students are more disciplined in following experimental procedures; (b) students are more active in carrying out all experimental activities: (c) students can cooperate better in groups and (d) students are more responsible in making reports and experimental presentations.